Pressure in the Spotlight: Effects of Monitoring Pressure and Outcome Pressure on Time-Sharing Performance - Pennanen, Niki (My University, 2024)
Performing under pressure, particularly in multitasking environments, is a critical challenge in both everyday life and high-stakes professions. This study investigated the differential effects of monitoring and outcome pressure on time-sharing performance and attentional allocation. Using a within-subjects design, 30 participants completed a cognitive task under three different pressure conditions while we recorded their eye movements. We hypothesized that in a high-demand time-sharing environment, outcome pressure would impair task performance and prioritization more significantly than monitoring pressure. However, our confirmatory analyses found no evidence to support this hypothesis. Interestingly, our additional exploratory analyses revealed that monitoring pressure, rather than outcome pressure, led to a statistically significant decrease in task performance. This unexpected finding is likely due to the sensorimotor demands of the task, specifically the need for precise and rapid mouse movements, which may have been disrupted by the participants’ heightened self-consciousness under monitoring pressure. Our findings contribute to the growing body of literature on the differential effects of monitoring and outcome pressure. Moreover, this study highlights the importance of carefully considering the influence of experimenter presence and other monitoring elements, as they potentially may inadvertently affect performance in computer-based tasks, even in studies not explicitly focused on psychological pressure. These insights underscore the complexity of psychological pressure effects and provide a foundation for refining experimental designs and exploring the distinct roles of different types of pressure in future research and practical applications.
Keywords: attentional control, time-sharing, multitasking, performance pressure, monitoring pressure, outcome pressure, eye movements